Influence of Training, Work Discipline, and Organizational Commitment on Employee Performance In The Work Environment of PT Asuransi Service Indonesia - Shabrina, An Nisaa; Zen, Agustian; Novita Ramadhan, Hanny; Novita Ramadhani, Muthia; Aprilia Hikayatuni’mah, Putri (Siber Journal of Advanced Multidisciplinary, 2023)
Our study looks at how organizational commitment, work ethic, and training influence how well the performance of employees at PT. Indonesian Service Insurance. The aim of this research is For ensure so far where commitment organization, discipline Work, And training influence employee performance while considering organizational commitment as a factor intervention. The research population consisted of every employee of PT. Indonesian Insurance Services. Whole member of PT. Service Indonesian Insurance Which follow in the research sample used. In study This influence trust organization, ethos Work, And training to performance PT employees Asuransi Jasa Indonesia will be questioned. Employee dedication and work ethic correlated strong with performance company; performance employee Which bad will impact negative on both of them.